Pengaruh Customer Value Dan Customer Experience Terhadap Keputusan Pembelian Ulang Pada Warung Lesehan Pak Brodin - Elisa Citra Anggraini; Ahmad Jauhari; Beny Mahyudi Saputra (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
In the current era of globalization, the success of a business requires creative ideas from business owners. Companies are required to produce creative ideas to provide value and positive experiences for consumers with the aim of increasing and retaining customers. This research aims to determine the influence of customer value (X1) and customer experience (X2) on repeat purchase decisions (Y) at Warung Lesehan Pak Brodin. Using a quantitative approach, the sampling technique used a non-probability sampling method in the form of accidental sampling of 88 Warung Lesehan Pak Brodin respondents. Data collection techniques include observation, interviews, questionnaires and literature studies, with the help of IBM SPSS version 25. The research results show that the Customer Value variable (X1) has a partial and significant effect on the Repurchase Decision (Y) with t count 4.280 > 1, 98827 and a sig t value of 0.000 < 0.05 and the Customer Experience variable (X2) has a partial and significant effect on the Repurchase Decision (Y) with a calculated t value of 4.640 > 1.98827 and a Sig t value of 0.000 < 0.05. Meanwhile, simultaneously, Customer Value (X1) and Customer Experience (X2) have a positive and significant effect on Repurchase Decisions with an F count of 49.563 > 3.10 and a Sig. F 0.000 < 0.05.